2020
DOI: 10.1098/rspb.2019.3014
|View full text |Cite
|
Sign up to set email alerts
|

Urban moth communities suggest that life in the city favours thermophilic multi-dimensional generalists

Abstract: Biodiversity is challenged worldwide by exploitation, global warming, changes in land use and increasing urbanization. It is hypothesized that communities in urban areas should consist primarily of generalist species with broad niches that are able to cope with novel, variable, fragmented, warmer and unpredictable environments shaped by human pressures. We surveyed moth communities in three cities in northern Europe and compared them with neighbouring moth assemblages constituting species pools of potential co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 60 publications
6
24
1
Order By: Relevance
“…The proportion of moth declines due to other aspects of urbanization is difficult to estimate, but a number of studies have documented that urbanization has large negative effects on moth diversity and abundance (e.g., ref. 63) and favors thermophilic and generalist species (64). Other stressors mentioned here may be intensified in urban areas; thus, species that are already at risk are more likely to decline in urban areas (65).…”
Section: Stressorsmentioning
confidence: 95%
“…The proportion of moth declines due to other aspects of urbanization is difficult to estimate, but a number of studies have documented that urbanization has large negative effects on moth diversity and abundance (e.g., ref. 63) and favors thermophilic and generalist species (64). Other stressors mentioned here may be intensified in urban areas; thus, species that are already at risk are more likely to decline in urban areas (65).…”
Section: Stressorsmentioning
confidence: 95%
“…For example, Franzén et al . (2020) suggested that polymorphic moths may have an advantage in urban environments with visual heterogeneity created by light pollution and non‐native plants (see also Galeotti et al . 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Studies analysing moths (Franzén et al . 2020) and birds (Leveau 2019) found that polymorphic species were more frequent and dominant, respectively, in urban areas than in non‐urban areas. Both studies were conducted in three cities of northern Europe (Franzén et al .…”
Section: Bibliographic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We collected aerosol samples at three locations in southern Sweden, two of which in parallel to two insect surveys, a Moth monitoring scheme and a Pollinator survey (called “Moth site” and “Pollinator site” henceforth). The Moth monitoring scheme was part of a systematic monitoring of Swedish moth species that has been ongoing for more than a decade (Franzén et al 2020). The project monitors moths using an automatic light trap (Robinson type) with a 250 W mercury vapour lamp (Leinonen et al 1998).…”
Section: Methodsmentioning
confidence: 99%